On writing : - Bishop, Wendy (McGraw-Hill, 2004)
What inspires writers? What frustrates them? Why is good writing so hard? When--and how--do writers write well? In On Writing: A Process Reader, composition theorist and poet Wendy Bishop presents a collection of readings that remind us not only why writing matters, but how it gets done. Organized around different aspects of the writing process (e.g., "Writing to Find Your Topic: Inventing, Exploring, Discovering"; "Writers and Readers: Drafting, Responding, and Revising"; etc.), the selections--by well-known published authors, as well as by students and their instructors--illuminate the art and the craft of writing.